Proses Menghadapi “Tekanan dan Badai” pada Remaja Akhir Asal NTT yang Mengalami Corporal Punishment Orang Tua - Wawin, Meyranda Adelia Florensia Riti Tapo; Arianti, Rudangta (Kajian Psikologi dan Kesehatan Mental, 2024)
Purpose: To understand the process of late adolescents facing "pressure and storms" and experiencing physical punishment from their parents. Research methodology: This qualitative phenomenological study involved two NTT male teens (ages 18–22) who experienced corporal punishment. Data were collected through semi-structured, in-depth interviews. Results: The results of the study showed that both participants used long-term stress coping and short-term stress coping as an effort to deal with "pressure and storms" due to corporal punishment by their parents. Both participants used short-term stress coping to avoid problems and minimize stress. Participant 1 used long-term stress coping to accept the situation and adapt to the family's wishes. Participant 2 used long-term stress coping to find his identity and avoid conflicts with his parents. Conclusions: Harsh parenting, such as physical punishment, causes children to feel pressured and afraid. NTT adolescents who experienced it expressed emotions, ran away, or chose to live apart to escape the pressure. Limitations: This study focuses less on the educational background of the participants and does not examine the role of culture in overcoming corporal punishment. Contribution: It is hoped that this research can enrich the reader's knowledge and apply it to life regarding the process of facing pressure and storms due to corporal punishment.